Does the Meeting Centres Support Programme reduce unmet care needs of community-dwelling older people with dementia? A controlled, 6-month follow-up Polish study - Mazurek J; Szcześniak D; Lion KM; Dröes RM; Karczewski M; Rymaszewska J (Clinical Interventions in Aging, 2019)
Justyna Mazurek,1 Dorota Szcześniak,2 Katarzyna Małgorzata Lion,2 Rose-Marie Dröes,3 Maciej Karczewski,4 Joanna Rymaszewska2 1Department and Division of Medical Rehabilitation, Wroclaw Medical University, Wrocław, Poland; 2Department of Psychiatry, Wroclaw Medical University, Wroclaw, Poland; 3Department of Psychiatry, VU University Medical Centre/GGZ in Geest, Amsterdam, the Netherlands; 4Department of Mathematics, Wroclaw University of Environmental and Life Sciences, Wroclaw, Poland Introduction: In Poland we lack a multidisciplinary and coordinated system of care for people with dementia, which would take the form of an evidence-based pathway and the number of reports on the holistic approach to caring for people living with this diagnosis is very low.Aim of the study: The aim of the study was to investigate whether the Meeting Centres Support Programme (MCSP) is effective in meeting the needs of older people with dementia.Participants and methods: This was done by comparing the experiences of people with dementia themselves and that of their carers at baseline and at follow-up, after 6 months of participation in MCSP or Usual Care (UC).Results: The study included 47 people diagnosed with mild-to-moderate dementia (n=24, MCSP group; n=23, UC control group) and 42 informal carers (n=22, MCSP group; n=20, UC control group), all living in Wroclaw in Poland and involved in the European JPND-MEETINGDEM project. To assess cognitive functioning and severity of dementia, the Mini-Mental State Examination and Global Deterioration Scale were used. The needs were assessed using the Camberwell Assessment of Need for the Elderly. The most frequently reported unmet needs at baseline both by the persons with dementia and their carers included activities of daily living, psychological distress, and the need for company. Compared to the UC group the unmet needs were reduced considerably in the MCSP group providing convincing evidence that MCSP is effective in reducing unmet needs over a 6-month period.Conclusion: MCSP may be regarded as a good example of comprehensive post-diagnostic support for patients with mild-to-moderate dementia as well as their informal carers.  Keywords: needs assessment, CANE, care management, health care, psychiatric services, social geriatrics, optimization, psychosocial care